Impact of Cilnidipine on Serum Lipid Profile in Alloxan- Induced Diabetic Rats - Maha Abdul-Wahab; Shatha H. Mohammad (The Indian Veterinary Journal, 2024)
Diabetes mellitus (DM) emerged as a significant global health crisis in the 20th century and stood as a leading cause of mortality, particularly due to cardiovascular disease (CVD) .Within the diabetic population, a troubling increase was observed in widely recognized microvascular complications, including neuropathy, nephropathy, and retinopathy. Simultaneously, the prevalence of macrovascular complications, such as stroke, carotid artery disease, peripheral artery disease, and coronary artery disease (CAD), also rose among individuals with diabetes.